Stable Semisimple Modules, Stable t- Semisimple Modules and Strongly Stable t-Semisimple Modules (Baghdad Science Journal, 2021)
Throughout this paper, three concepts are introduced namely stable semisimple modules, stable t-semisimple modules and strongly stable t-semisimple. Many features co-related with these concepts are presented. Also many connections between these concepts are given. Moreover several relationships between these classes of modules and other co-related classes and other related concepts are introduced.